2021
DOI: 10.1021/acs.jafc.1c04608
|View full text |Cite
|
Sign up to set email alerts
|

The Jasmonic Acid Signaling Pathway is Associated with Terpinen-4-ol-Induced Disease Resistance against Botrytis cinerea in Strawberry Fruit

Abstract: Terpinen-4-ol, the main component of tea tree oil, markedly increases the disease resistance of postharvest strawberry fruit. To understand the mechanism underlying the enhancement of disease resistance, a high-throughput RNA-seq was used to analyze gene transcription in terpinen-4-ol-treated and untreated fruit. The results show that terpinen-4-ol induces the expression of genes in the jasmonic acid (JA) biosynthesis pathway, secondary metabolic pathways such as phenylpropanoid biosynthesis, and pathways invo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(10 citation statements)
references
References 47 publications
1
9
0
Order By: Relevance
“…Lignin can strengthen cell wall and act as a natural physical barrier for any fungus entry and infection, where the key enzymes involved in lignin biosynthesis include PAL, C4H, CAD, and POD 19,20,42 . Enhanced enzymes activities and up‐regulated gene expressions involved in lignin biosynthesis effectively contributed to the lignin deposition, thereby inducing the resistance in citrus fruit, litchi, 40 kiwifruit, 12 and strawberry 38,43 . Our results precisely showed that CVR treatment increased the activities of PAL, CAD and POD, and up‐regulated the expression levels of CgPAL1 , CgCAD2 and CgPOD1 after 3 days of D. citri inoculation (Fig.…”
Section: Discussionsupporting
confidence: 58%
“…Lignin can strengthen cell wall and act as a natural physical barrier for any fungus entry and infection, where the key enzymes involved in lignin biosynthesis include PAL, C4H, CAD, and POD 19,20,42 . Enhanced enzymes activities and up‐regulated gene expressions involved in lignin biosynthesis effectively contributed to the lignin deposition, thereby inducing the resistance in citrus fruit, litchi, 40 kiwifruit, 12 and strawberry 38,43 . Our results precisely showed that CVR treatment increased the activities of PAL, CAD and POD, and up‐regulated the expression levels of CgPAL1 , CgCAD2 and CgPOD1 after 3 days of D. citri inoculation (Fig.…”
Section: Discussionsupporting
confidence: 58%
“…Increased TAP in treated strawberry fruits may be the reason for the maintenance of ascorbic acid content, since phenolics have a protective effect [35], but this may also be attributed to a delay in the senescence process [26]. Similar effects of SA on total phenolic content have also been shown in table grape [42], cucumber [43], orange [35], pomegranate [25] apricot [40], and peach [44].…”
Section: Discussionmentioning
confidence: 91%
“…Thereby, these metabolites help to protect fruit from pathogens. This was also the case for terpinen-4-ol [42,43]. Increased TAP in treated strawberry fruits may be the reason for the maintenance of ascorbic acid content, since phenolics have a protective effect [35], but this may also be attributed to a delay in the senescence process [26].…”
Section: Discussionmentioning
confidence: 98%
“…These reports were consistent with our results that up-regulated expression of PR1 α, NAC, OsSAUR2 , and EL5 can enhance the systemic disease resistance of rice after P. oryzae inoculated rice roots. In addition, salicylic acid (SA) ( Janda et al, 2020 ), jasmonic acid (JA) ( Barna et al, 2012 ; Li et al, 2021 ) and ethylene (ET) ( Wang et al, 2019 ) also play important roles in inducing resistance ( Glazebrook, 2005 ; McDowell et al, 2005 ; Flors et al, 2008 ). AOS ( Gfeller et al, 2010 ; Xiao et al, 2019 ) and ERF4 ( Yang et al, 2005 ) are key genes of JA biosynthesis pathway and ethylene pathway, respectively.…”
Section: Discussionmentioning
confidence: 99%